(untitled) (CIPEEX, 2025)
The effectiveness of Brazilian representative democracy is intrinsically linked to the existence of legal instruments that ensure the integrity of the electoral process and curb practices that undermine equal conditions for candidates. This paper analyzes the main regulatory and jurisprudential mechanisms for electoral control and integrity in Brazil, highlighting the advances promoted by Constitutional Amendment No. 97/2017 and the Supreme Federal Court’s decision in ADI No. 4,650, which banned electoral financing by legal entities. The research demonstrates that, despite this progress, challenges remain related to transparency, traceability of resources, and the equitable distribution of financing among parties. The central role of the Electoral Court is also highlighted, especially in enforcing the Ineligibility Law (LC No. 64/1990) and the Clean Record Law (LC No. 135/2010), especially in combating the abuse of political and economic power, through initiatives such as the AIJE and AIME. The study concludes that, although the Brazilian legal framework is robust, the consolidation of democratic integrity depends on constant vigilance, active civil society participation, and continuous improvement of electoral norms and practices. The research thus provides insights for reflection on improving the electoral system, suggesting future research on the impact of new technologies and disinformation on the democratic proces